The dynamics of color signals in male threespine sticklebacks Gasterosteus aculeatus - Hiermes, Meike (Curr Zool, 2016)
Body coloration and color patterns are ubiquitous throughout the animal kingdom and vary between and within species. Recent studies have dealt with individual dynamics of various aspects of coloration, as it is in many cases a flexible trait and changes in color expression may be context-dependent. During the reproductive phase, temporal changes of coloration in the visible spectral range (400–700 nm) have been shown for many animals but corresponding changes in the ultraviolet (UV) waveband (300–400 nm) have rarely been studied. Threespine stickleback Gasterosteus aculeatus males develop conspicuous orange–red breeding coloration combined with UV reflectance in the cheek region. We investigated dynamics of color patterns including UV throughout a male breeding cycle, as well as short-term changes in coloration in response to a computer-animated rival using reflectance spectrophotometry and visual modeling, to estimate how colors would be perceived by conspecifics. We found the orange–red component of coloration to vary during the breeding cycle with respect to hue (theta/R50) and intensity (achieved chroma/red chroma). Furthermore, color intensity in the orange–red spectral part (achieved chroma) tended to be increased after the presentation of an artificial rival. Dynamic changes in specific measures of hue and intensity in the UV waveband were not found. In general, the orange–red component of the signal seems to be dynamic with respect to color intensity and hue. This accounts in particular for color changes during the breeding cycle, presumably to signal reproductive status, and with limitations as well in the intrasexual context, most likely to signal dominance or inferiority.